Students’ English Speaking Anxiety in Classroom Context - Andi Satrianto Pattah; Murni Mahmud; Nurdin Noni (Celebes Scholar pg, 2022)
This research was designed to investigate students’ English speaking anxiety in a classroom context. There were 23 students from Unismuh Makassar who participated in this research by using the purposive sampling method. This mixed-methods study looked into the students' English-speaking anxiety and how they overcame it. A structured interview and a questionnaire adapted from the Horwitz et al. (1986) Foreign Language Classroom Anxiety Scale (FLCAS) were used to gather the data. According to the findings of the study, (1) the majority of English Education students at Unismuh Makassar experienced excessive anxiety, with 74.2% anxious, 21.7% anxious in the middle, and no one anxious in the low. (2) Based on the students' experiences, there were six strategies to deal with anxiety: keep silent, take a deep breath, relax with the circumstances, reiterate the lesson, avoid eye contact, and drink water. The finding indicated the excessive level of students’ anxiety and the strategies to cope with it. According to these findings, lecturers should be more aware of their students' worries in order to push them to speak up confidently and clearly in English class. Telling a joke, expressing gratitude, and making a pleasant gesture are all strategies to assist kids overcome their fear of public speaking. As a result, teachers are encouraged to be slightly innovative in developing new strategies to enable students to speak more effectively.